Pengaruh Pemberian Minuman Jahe (Zingiber Officinale Rose) dan Daun Pandan (Pandanus) Terhadap Penurunan Mual Muntah Pada Ibu Hamil (Emesis Gravidarum) TM I BPM HJ. Nina Nuraenayatin, SST., M.Pd Surabaya Tahun 2017 - Jamila, Fidatul; Cahaya, Eka Nur (Infokes, 2018)
Nausea and vomiting or in medical language called emesis gravidarum or morning sickness is a state of nausea sometimes accompanied by vomiting (frequency less than 5 times). The purpose of this study was to determine the effect of giving ginger drink (zingiber officinale rose) and pandanus leaf (pandanus) to the emission reduction of trimester pregnant women I. This research is pre experimental research with design of one group pre test post test. Population in this research is first trimester pregnant woman with 10 respondents. The study was conducted for 7 days.  Sampling technique by purposive sampling. Data collection using observation sheet and data analysis using wilcoxon test. The results showed Frequency of emesis gravidarum before giving of ginger and pandanus leaves mostly with emesis gravidarum frequency 5 times (60%) and a small part of the emesis gravidarum frequency 3 times (10%). Frequency of emesis gravidarum after giving of ginger and pandanus leaves all pregnant women do not experience emesis gravidarum. Wilcoxon test results P = 0.004 (P <0.05). The conclusion of this research is the influence of the giving of ginger and pandan leaves to the decrease of Emesis Gravidarum in First Trimester in Work Area of ​​BPM Hj. Nina Nuraenayatin, SST., M.Pd Surabaya. It is hoped for midwives to provide accurate motivation and information on pregnant women about emesis gravidarum and how to reduce emesis during pregnancy.